2013
DOI: 10.1364/oe.21.006794
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of high-Q optical nanocavities with a gradual 1D bandgap

Abstract: High-quality cavities in hybrid material systems have various interesting applications. We perform a comprehensive modeling comparison on such a design, where confinemen in the III-V material is provided by gradual photonic crystal tuning, a recently proposed method offering strong resonances. The III-V cavity couples to an underlying silicon waveguide. We report on the device properties using four simulation methods: finite-di ference time-domain (FDTD), finite-elemen method (FEM), bidirectional eigenmode pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Rigorous numerical calculations of the optical response were performed using our efficient in-house developed software based on the RCWA method, 28,29 incorporating several special treatments such as proper Li's factorization, adaptive spatial resolution, and incorporation of special symmetries. The metallic dispersion behaviour is characterized according to experimental data.…”
Section: Light Interacting With 1-d Array Of Slitsmentioning
confidence: 99%
“…Rigorous numerical calculations of the optical response were performed using our efficient in-house developed software based on the RCWA method, 28,29 incorporating several special treatments such as proper Li's factorization, adaptive spatial resolution, and incorporation of special symmetries. The metallic dispersion behaviour is characterized according to experimental data.…”
Section: Light Interacting With 1-d Array Of Slitsmentioning
confidence: 99%
“…A similar study of PhC nanobeam cavities using four numerical techniques was reported in [18], where cavity frequencies and Q factors were investigated as function of physical parameters. Qualitative agreement between the four methods was found, but with quantitative discrepancies in some cases being as large as an order of magnitude, and no computational uncertainty estimates were given.…”
Section: Introductionmentioning
confidence: 94%
“…The software used for simulations in this paper is our in-house implementation of RCWA algorithms both in periodic (applicable for simulation of periodic structures) and aperiodic versions (applicable for simulation of isolated "aperiodic" structures), developed in MATLAB programming enviroment 15 . Our RCWA tool allows for calculating the energy (in terms of reflectivities R, transmissivities T , and losses L) and amplitude (fields and all S-parameters of a structure) characteristics of periodical 2D structures, together with displaying the required calculated field profiles.…”
Section: Rigorous Coupled Wave Analysis Simulation Toolmentioning
confidence: 99%
“…The software reliability has been tested many times, involving various advanced computational problems (see, e.g. Špačková et al 14 , Maes et al 15 , Fiala et al 16 ).…”
Section: Rigorous Coupled Wave Analysis Simulation Toolmentioning
confidence: 99%
See 1 more Smart Citation